2015
DOI: 10.1007/s10661-015-4792-z
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment and reuse of secondary effluents using natural ltreatment systems: the Indian practices

Abstract: Paper summarizes the results of India-wide survey of natural treatment systems (NTSs) for wastewater treatment and reuse. The quality of treated wastewater from different types of NTSs was analyzed for various physico-chemical and bacteriological parameters, and needs for post-treatment were identified. Currently, about 1838 million liters per day (MLD) of wastewater is being treated using NTSs, of which the contributions of polishing ponds, waste stabilization ponds, duckweed ponds, constructed wetlands, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The typical range of removal of organic pollutants, namely BOD 5 and COD was found between 86-94.55 and 72.7-89.2 %, respectively. Likewise, the TKN removal was also found highest in summer as compared with winter and rainy seasons, but their removals were not equally high as in the other natural treatment systems like constructed wetlands (Kumar et al 2015). TKN removals during winter, summer and rainy reason were found to be 7.3, 14.5 and 3.1 %, respectively.…”
Section: Performance Of the Treatment Facilitymentioning
confidence: 77%
See 2 more Smart Citations
“…The typical range of removal of organic pollutants, namely BOD 5 and COD was found between 86-94.55 and 72.7-89.2 %, respectively. Likewise, the TKN removal was also found highest in summer as compared with winter and rainy seasons, but their removals were not equally high as in the other natural treatment systems like constructed wetlands (Kumar et al 2015). TKN removals during winter, summer and rainy reason were found to be 7.3, 14.5 and 3.1 %, respectively.…”
Section: Performance Of the Treatment Facilitymentioning
confidence: 77%
“…The broad spectrum of pathogenic micro-organisms, including bacteria, viruses, helminths and protozoa present in wastewater survive in the environment for days, weeks and months in the soil and on crops that come in contact with wastewater. Furthermore, the presence of a high number of faecal bacteria in secondary treated wastewater used for irrigation or discharge into water bodies without any post-treatment (especially disinfection) may cause the most severe problems including groundwater and surface water contaminations (Kumar et al 2015). The crop irrigated with wastewater containing high number of faecal bacteria may also pose the problem of food contamination if the grown vegetables (e.g.…”
Section: Health Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically 1-2 mg/L of chlorine dose is being administered before the effluents are let off for irrigation or gardening or discharged into the legally permitted water bodies (Kumar et al, 2011;Kumar et al, 2012;Kumar et al, 2015a). It was evident from the survey that the secondary treated sewages were typically reused in irrigation (22 facilities) and recharging into lakes or rivers (48 facilities).…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al (2015) studied natural treatment systems across India and found that constructed wetlands met total coliform requirements but polishing ponds, waste stabilization ponds, and duckweed ponds did not. A literature review of virus removal in 71 different wastewater treatment pond systems found 1 log removal every 14…”
mentioning
confidence: 99%